A dictionary of film studies - Kuhn, Annette; Westwell, Guy (Oxford University Press, 2020)
The Oxford Dictionary of Film Studies covers all aspects of the discipline of film studies. Being a work of reference in film studies (and not in film), it is grounded in a systematic overview of the field, both historically and as it is currently taught and researched. We began by conducting a comprehensive survey of the discipline, involving a twofold process. Firstly, we reviewed a dozen or so major Englishlanguage introductory textbooks, looked at film studies curricula in UK secondary and tertiary education, and examined a number of existing reference works, among them Beaver (2015), Grant et al. (2000), Hayward (2017), and Konigsberg (1997). This exercise produced a listing of topics and areas of film study regarded by experts in the field as appropriate for inclusion in introductory courses. Secondly, we conducted a wider survey of the film studies research literature: this, along with our own knowledge of the discipline built up during a combined total of more than sixty years' experience as teachers and researchers, brought to light a loose cluster of broad sub-areas of research, scholarship, and teaching and provided us with a sense of the changes that have taken place in the field over the years-- Provided by publisher.